Docking Molecular Simulation Of Secondary Metabolic Compounds Annona Muricata As Anti-Cancer - Sofyan Hidayatulloh (Green Publisher Indonesia, 2021)
This study aims to test and determine the affinity and molecular mechanism of Annona muricata to COX-2 target protein, which can be used to test the potential of Annona muricata as an anticancer drug using the molecular docking in silico method (computer modeling). By identifying and optimizing guide molecules in the drug discovery process, this computational chemical technique can be utilized to accelerate the selection of compounds to be isolated and synthesized. The research use descriptive quantitative as a research design and the experimental factorial design as an approach. The results of this study indicate that curcumin and its analogues have potential to became anticancer, and can be used for further drug development related to anticancer.